Echoes of the Shoah: British Jewry and the Bosnian War - Summers, Luke (Holocaust studies, 2026)
This article explores how British Jews responded to the Bosnian War of 1992-1995. It questions how Jewish memories of the Holocaust influenced the way the community responded to the genocide in Bosnia. Using the British Jewish press as its source base, it identifies how British Jews extensively referenced the Shoah when responding to events in Bosnia. Highlighting a lack of international action to stop the Holocaust, British Jews attached a moral imperative to military intervention in Bosnia. It probes the idea that genocide in the Balkans had an important role in the expansion, and universalization, of Holocaust consciousness in the 1990s.